Manajemen Dakwah Pada Masa Kerajaan Turki Usmani 1300-1922 M - Nasution, Habib Ilmi; Surya, Maulana Andi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The Ottoman Empire was one of the great powers in Islamic history, wielding widespread influence not only in the Islamic world but also in Eastern Europe. The empire's success in achieving future glory was not solely determined by military and political power, but also by the integrated management of da'wah (Islamic outreach) in various aspects of state life. This study aims to describe and analyze the implementation of da'wah management during the Ottoman Empire and to support the empire's development. The research method used is a qualitative method with a literature study approach, examining various primary and secondary sources relevant to the history and da'wah system of the Ottoman Empire. The results of the study indicate that da'wah management during the Ottoman Empire was implemented systematically and structured across the military, government, education, religious, and cultural sectors. Da'wah was not merely a religious activity but also part of the state's strategy to build stability, expand its territory, and shape the character of its people. In conclusion, the Ottoman Empire's success as a major Islamic power was greatly influenced by the effectiveness of da'wah management integrated with the government system and social development.